PENINGKATAN KEAHLIAN BAGI PARA PEMUDA MELALUI PENGENALAN BISNIS UMKM DENGAN SISTEM ONLINE DI GAMPONG RANTO PANYANG TIMUR KABUPATEN ACEH BARAT - Alfian Anas; Muhammad Rahmat Hidayat; Helmi Noviar; Rusdi Rusdi; Damrus Damrus (Universitas Teuku Umar, 2021)
The purpose of this community service is to develop the ability of youth to develop an ability to build a business using online methods, especially in marketing area. This is important because technology can help entrepreneurs to access more customers and it is easy to practice with only little knowledge. Covid-19 pandemic also bring a new situation and entrepreneurs should be creative to cope with this change. The problem of many young entrepreneurs are they still feel reluctant to use technology as they think it is expensive and complicated. Other problems are some of them have difficulty to build a new business as they have a lack of fund and access to financial institutions, not knowing how to conduct an accounting or manage the financial things and cannot handle the marketing of their business. So, this socialisation brings some solution to young people to improve their ability to conduct a business using online methods, provide business skills especially in online marketing area, and motivate them to eager to conduct business during Covid-19 pandemic.